2012
DOI: 10.1088/0953-2048/25/6/065002
|View full text |Cite
|
Sign up to set email alerts
|

Drawing induced texture and the evolution of superconductive properties with heat treatment time in powder-in-tubein situprocessed MgB2strands

Abstract: Monocore powder-in-tube MgB 2 precursor strands were cold-drawn and heat- This effect is attributed to the fibrous macrostructure and its accompanying anisotropic connectivity. Magnetic measurements with the field directed along the strand axis yielded a critical density, J cm ┴ (B), for current flowing transversely to the strand axis that was less than and dropped off more rapidly than J ct (B). In the conventional magnetic measurement, the loop currents that support the magnetization are restricted by the lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 80 publications
2
38
0
Order By: Relevance
“…This suggests that the starting composition of the material may influence B c2 . The results in Figure 6a show that 1 GPa pressure can increase B irr from 10 K to 27 K, and slightly reduce B irr above 27 K. By contrast, an increase in annealing temperature (Figure 6b) reduces B irr in between 15 K to 25 K and does not change B irr from 10 K to 15 K and above 25 K. Maeda and Susner claim that the value of the B irr is dependent on dislocation [28,29]. Moreover, Serquis showed that the HIP process can increase the density of dislocations [13].…”
Section: Research Resultsmentioning
confidence: 95%
“…This suggests that the starting composition of the material may influence B c2 . The results in Figure 6a show that 1 GPa pressure can increase B irr from 10 K to 27 K, and slightly reduce B irr above 27 K. By contrast, an increase in annealing temperature (Figure 6b) reduces B irr in between 15 K to 25 K and does not change B irr from 10 K to 15 K and above 25 K. Maeda and Susner claim that the value of the B irr is dependent on dislocation [28,29]. Moreover, Serquis showed that the HIP process can increase the density of dislocations [13].…”
Section: Research Resultsmentioning
confidence: 95%
“…This value could not be regarded as the exact atomic ratio in MgB 2 phase because the average volumes with dimensions larger than MgB 2 grain size observed by TEM (see Section 3.1.2) are measured. Casino software calculation [21] helped us to estimate that 5 keV electron beam with optimized beam current of 3.55 nA gave information signal from MgB 2 volume of about 400 Â 400 Â 400 nm 3 .…”
Section: Compositionmentioning
confidence: 99%
“…Powder-in-tube (PIT) process is frequently used for the manufacture of superconducting MgB 2 wires [1][2][3][4][5]. Apparent in-field increase of critical current densities has been reached by different types of doping [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal cross section areas of W00 and W15 are shown in Figure 12 and Figure 13. Susner et al [10] described that continuous MgB2 stringers in PIT in-situ wire were aligned along drawing direction and elongated voids which were left…”
Section: Measurementmentioning
confidence: 99%